Difficulties of Millennials on the Competitiveness of Tech Companies during 2017 - Gutiérrez Benavides, Fernando (2019)
The following investigation pertains the study of different articles and the application of a field study, in order to determine the positive correlation between the variables: employment rotation, lack of motivation and lack of compromise of the Costa Rican Millennials; as well as, the impact in the competitiveness of the technological companies.  The investigator made a study and applied a survey, in the tech company Fiserv CR, in order to obtain relevant information, and with a Pearson Coefficient, he was able to prove the affinity level between the mentioned variables, test his hypothesis and stablish conclusions recommendations.